Differential Expression of Insulin-Like Growth Factor 1 and Wnt Family Member 4 Correlates With Functional Heterogeneity of Human Dermal Fibroblasts - Culley, Oliver J.; Louis, Blaise; Philippeos, Christina; Oulès, Bénédicte; Tihy, Matthieu; Segal, Joe M.; Hyliands, Della; Jenkins, Gail; Bhogal, Ranjit K.; Siow, Richard C.; Watt, Fiona M. (Frontiers in Cell and Developmental Biology, 2021)
Although human dermis contains distinct fibroblast subpopulations, the functional heterogeneity of fibroblast lines from different donors is under-appreciated. We identified one commercially sourced fibroblast line (c64a) that failed to express α-smooth muscle actin (α-SMA), a marker linked to fibroblast contractility, even when treated with transforming growth factor-β1 (TGF-β1). Gene expression profiling identified Insulin-like growth factor 1 (IGF1) as being upregulated, and Asporin (ASPN) and Wnt family member 4 (WNT4) downregulated, in c64a fibroblasts compared to three in-house fibroblast lines, independent of TGF-β1 treatment. TGF-β1 selectively upregulated C-X-C motif chemokine ligand 1 (CXCL1) in c64a cells. The c64a gene expression profile did not correspond to any dermal fibroblast subpopulation identified by single cell RNAseq of freshly isolated human skin cells. c64a fibroblasts did not support epidermal stratification in skin reconstitution assays. In fibroblast lines generated in-house, shRNA-mediated knockdown of IGF1 increased α-SMA expression without affecting epidermal stratification. Conversely WNT4 knockdown had no consistent effect on α-SMA expression, but increased the ability of fibroblasts to support epidermal stratification. Thus, by comparing the properties of different lines of cultured dermal fibroblasts we have identified IGF1 and WNT4 as candidate mediators of two distinct dermal functions: myofibroblast formation and epidermal maintenance.